The life course paradigm and consumer behavior: Research frontiers and future directions - George P. Moschis (2022)
Although researchers have been increasingly using life course perspectives for studying various types of consumption-related behaviors, they are yet to fully benefit from a recently developed multidisciplinary research approach, known as “the life course paradigm.” This paradigm is viewed as a theoretical orientation for the study of stability and change in thoughts and actions over time. It is used extensively across disciplines and internationally, but it has received limited attention in the consumer field; and it has the potential of helping researchers improve their efforts to study consumers over time. To help inform the reader about this paradigm and its assumptions, this article first presents a conceptual life course model and demonstrates its application. Next, it briefly discusses studies that have employed life course explanations of a variety of consumption-related activities, and interprets their results within the context of the life course model, identifying gaps and research questions that could be effectively studied using the life course paradigm. Finally, the article presents a research agenda on topics of interest to several groups of researchers, offering novel insights and innovative methods to help them think about how to study various types of consumer behavior over time within the life course conceptual blueprint.